دور القاضي الإداري في تفسير المعاهدات الدولية - أمين برانسية; كافي محمد (My University, 2018)
Summary: This note addresses an important issue within the framework of international relations and the rules of international law and administrative law as a whole because they are highly sensitive in the development of relations between the parties of the international community, namely the interpretation of international treaties by the administrative judge, so that international treaties occupy a privileged position and are the most important sources of international law and the best means of legal association between States or organizations in order to cooperate and overcome disputes. Where treaty interpretation is considered to be a defining weapon, either it shall be interpreted in a sound manner to achieve the real purpose behind its conclusion, or it shall be interpreted in conformity with the interests of the State, which may lead to a disconnect in international relations. The administrative judge applies the law and interprets it as many judges. However, his obligation to apply and interpret international treaties is governed by controls that differ from one State to another. The interpretation of international treaties must be in accordance with certain frameworks, methods and principles in order to achieve the desired purpose. However, this does not remove them from a number of problems and obstacles. ....................... الملخص: تتناول هذه المذكرة مسألة مهمة في إطار العلاقات الدولیة وقواعد القانون الدولي والقانون الإداري ككل لكونها ذات حساسیة بالغة في تطویر العلاقات بین أطراف المجتمع الدولي ألا وهي تفسیر المعاهدات الدولیة من طرف القاضي الإداري، حیث تحتل المعاهدات الدولیة مكانة متمیزة وتعد أهم مصادر القانون الدولي وأفضل الوسائل للارتباط القانوني فیما بین الدول أو المنظمات بهدف التعاون وتجاوز الخلافات. حیث یعتبر تفسیر المعاهدات سلاح ذو حدین، إما أن تفسر بطریقة سلیمة تحقق الغرض الحقیقي من وراء ابرامها، أو تفسر بما یتماشى ومصالح الدولة وهذا ما قد یؤدي إلى الاحتقان في العلاقات الدولیة. إن القاضي الإداري یطبق القانون ویفسره كغیره من القضاة إلا أن التزامه بتطبیق وتفسیر المعاهدات الدولیة یحكمه ضوابط تختلف من دولة لأخرى، كذلك یجب أن یكون تفسیر المعاهدات الدولیة وفق أطر وطرائق ومبادئ معینة حتى تحقق الغایة المنشودة، غیر أن ذلك لا یبعدها عن العدید من الإشكالات والمعوقات أهمها الجهة المختصة بتفسیر المعاهدات ودور القاضي من هذه العملیة. ...................... Résumé : Cette note aborde une question importante dans le cadre des relations internationales et des règles de droit international et de droit administratif dans leur ensemble, car elles sont très sensibles au développement des relations entre les parties de la communauté internationale, à savoir l’interprétation des traités internationaux par le juge administratif, afin que les traités internationaux occupent une position privilégiée et soient les sources les plus importantes du droit international et les meilleurs moyens d’association juridique entre États ou organisations pour coopérer et surmonter les différends. Lorsque l’interprétation des traités est considérée comme une arme déterminante, soit elle est interprétée de manière rationnelle pour atteindre le but réel de sa conclusion, soit elle est interprétée conformément aux intérêts de l’État, qui peut conduire à une rupture des relations internationales. Le juge administratif applique la loi et l’interprète comme autant de juges. Cependant, son obligation d’appliquer et d’interpréter les traités internationaux est régie par des contrôles qui diffèrent d’un État à l’autre. L’interprétation des traités internationaux doit être conforme à certains cadres, méthodes et principes pour atteindre l’objectif recherché. Cependant, cela ne les enlève pas d’un certain nombre de problèmes et d’obstacles.